Comunicação museológica: levantamento bibliográfico no Portal de Periódicos da Capes - Padovesi, Mariana; Doretto, Juliana (Anagrama, 2020)
This work proposes to explore the theme of communication in museums and reflect on its importance in contemporary scientific production, identifying and relating the main theories and approaches on the theme, in addition to their respective authors. Through a qualitative analysis of the data, we sought to answer the following questions: What is the space that museological communication occupies in the area of communication and information? How is this topic treated? To this end, an investigation was carried out on the Portal de Periódicos da Capes (Capes Journals Portal), which established a connection between the authors with works relevant to the subject and their respective theoretical lines. The 36 selected articles show that the theme of museological communication is current and arouses interest in magazines that convey quality scientific production.